Spiced ebook Unlock the power of spices to transform your cooking. - America's Test Kitchen (2019)
Harness the power of spices to take your dishes from simple to spectacular with 139 exciting recipes, plus find 47 easy spice blends and condiments you can use many ways. Spices: You probably have a cabinet full of them, but do you know how to make the most of them? Spiced opens up the world of possibility hidden in your own pantry, with six chapters, each of which shares a way to use spices to amp up the flavor of your cooking, along with foolproof recipes that put these simple techniques to work. Sprinkle a finishing salt you make from sea salt and herbs on seared white fish fillets to make them special. Make a different roast chicken every week by applying a different rub. Learn the best spices to use in curries—and when to add them for fragrant (not dusty) results. Add flavor—and texture—with homemade blends (you'll eat your spinach when it's topped with pistachio dukkah). Infuse condiments with spices (try chipotle ketchup on a burger). With the following six simple techniques, plus vibrant recipes, you'll find yourself not only spooning chili powder into the chili pot but making the chili powder yourself, or flavoring desserts with saffron or cardamom rather than just cinnamon.      #1: Season smarter with salt and pepper. You'll learn about brining, using peppercorns of all colors, and making finishers like sriracha salt.      #2: Give meat and vegetables a rub. We'll provide blends that you can put to use in our recipes (try juniper and fennel on salmon) or your own.      #3: Bloom and toast. Bring out ground spices' complexity by cooking them in oil; unlock dried chiles' fruity or nutty flavors by toasting them.      #4: Finish foods with flair. Spice-and-nut/seed blends likes shichimi togarashi (a mix of spices, orange zest, and sesame seeds) add texture, too.      #5: Let spices steep. Infuse spices into condiments like pickled fennel that punches up chicken salad or rosemary oil to drizzle over bruschetta.      #6: Bake with spices. Go beyond vanilla by rolling doughnuts in strawberry-black pepper sugar. Make your own rose water and add it to pistachio baklava.